A novel model for bicycle drivetrain efficiency - Dowd, T.; Cavanaugh, P.; Mansson, J.-A. (Sports Engineering, 2025)
This study introduces a new model for bicycle drivetrain efficiency, termed the "DCM" model. This model is used for characterizing cycling drivetrain efficiency across varying conditions—a critical factor in optimizing the performance of bicycles in competitive, recreational, and transportation contexts. A testing rig was developed to measure drivetrain efficiency under different simulated riding conditions, with a focus on the performance of chains using various lubricants tested over torque and angular velocity combinations. Analysis revealed a linear relationship () between efficiency and the DCM metric, defined as providing a framework for predicting drivetrain efficiency. Through regression analysis, the slope and the intercept of this linear relationship were used as all-encompassing parameters that characterize drivetrain performance, facilitating the selection of lubricant based on anticipated cycling conditions. The DCM model establishes a robust framework for advancing both practical applications and scientific understanding of cycling drivetrain efficiency. The DCM model`s broad applicability in analyzing efficiency across different situations offers opportunities for optimizing drivetrain performance, especially in aligning mechanical and physiological efficiencies for prolonged power outputs.